Strategic Leadership for Character: Principal Approaches to Discipline Formation in Challenging Educational Contexts - Nurmin Nurmin; Agung Purwa Widiyan (Papanda Publisher, 2026)
School principals play a critical role in character education, yet limited research examines disciplinary character formation in remote, culturally diverse contexts. This study investigated principals' roles and strategies in fostering disciplinary character among students in Tambrauw Regency junior secondary schools and assessed the impacts of their leadership. A qualitative case study approach was employed at two schools: SMP Negeri 1 Sausapor and SMP YPK Maranatha Sausapor. Data were collected over three months through in-depth interviews with principals, vice principals, teachers, and students, complemented by non-participant observations and document analysis. Data were analyzed using Miles and Huberman's interactive model, with validity ensured through source, method, and time triangulation. Findings revealed that principals effectively performed multifaceted roles as educators, managers, supervisors, and exemplary models. Strategic approaches encompassed consistent personal modeling, habituation programs, balanced reinforcement systems, and culturally responsive collaboration with stakeholders. Quantifiable impacts included a 16-percentage-point reduction in student tardiness, 73% decrease in uniform violations, and establishment of positive school culture. Principals demonstrated cultural intelligence by integrating local Papuan customs with national educational standards. This study demonstrates that transformational leadership, when contextually adapted to honor indigenous values, effectively cultivates disciplinary character in remote multicultural settings, contributing empirical evidence to educational leadership discourse in underserved regions.